The Comparison between National Final Examination Test Items and English Teacher Made-Test Items of 2010 and 2011 - Khairil Razali; Miftahul Jannah (Institut Agama Islam Negeri Imam Bonjol Padang, 2015)
The objective of the paper is to determine the relevance between the scope of the national final examination test items in English lesson and the English teacher made test items. It is also to identify the relevance between the deepness of national final examination test items in English subject and the English teacher made test item. The finding showed that more than fifty percents of tryout out test items are not relevant with the national test items. Meanwhile, the final national test items were design with higher cognitive domain than teacher made test items. It means the teacher made test items (tryout) is more superficial than final national test items. It can be a reason why the students who are can pass the tryout test which is made in teacher cannot pass the national final examination test (standardized test). It is expected that this study provides empirical evidence to devise on their optimal uses in EFL teaching. Copyright © 2015 by Al-Ta'lim All right reserved